Variations in the practice of molecular radiotherapy and implementation of dosimetry: results from a European survey - Sjögreen Gleisner, Katarina; Spezi, Emiliano; Solny, Pavel; Gabina, Pablo Minguez; Cicone, Francesco; Stokke, Caroline; Chiesa, Carlo; Paphiti, Maria; Brans, Boudewijn; Sandström, Mattias; Tipping, Jill; Konijnenberg, Mark; et al. (EJNMMI physics, 2017)
BACKGROUND: Currently, the implementation of dosimetry in molecular radiotherapy (MRT) is not well investigated, and in view of the Council Directive (2013/59/Euratom), there is a need to understand the current availability of dosimetry-based MRT in clinical practice and research studies. The aim of this study was to assess the current practice of MRT and dosimetry across European countries. METHODS: An electronic questionnaire was distributed to European countries. This addressed 18 explicitly considered therapies, and for each therapy, a similar set of questions were included. Questions covered the number of patients and treatments during 2015, involvement of medical specialties and medical physicists, implementation of absorbed dose planning, post-therapy imaging and dosimetry, and the basis of therapy prescription. RESULTS: Responses were obtained from 26 countries and 208 hospitals, administering in total 42,853 treatments. The most common therapies were 131I-NaI for benign thyroid diseases and thyroid ablation of adults. The involvement of a medical physicist (mean over all 18 therapies) was reported to be either minority or never by 32% of the responders. The percentage of responders that reported that dosimetry was included on an always/majority basis differed between the therapies and showed a median value of 36%. The highest percentages were obtained for 177Lu-PSMA therapy (100%), 90Y microspheres of glass (84%) and resin (82%), 131I-mIBG for neuroblastoma (59%), and 131I-NaI for benign thyroid diseases (54%). The majority of therapies were prescribed based on fixed-activity protocols. The highest number of absorbed-dose based prescriptions were reported for 90Y microsphere treatments in the liver (64% and 96% of responses for resin and glass, respectively), 131I-NaI treatment of benign thyroid diseases (38% of responses), and for 131I-mIBG treatment of neuroblastoma (18% of responses). CONCLUSIONS: There is a wide variation in MRT practice across Europe and for different therapies, including the extent of medical-physicist involvement and the implementation of dosimetry-guided treatments.
Keywords: European survey; Radionuclide therapy; Molecular radiotherapy; Dosimetry; Radiopharmaceutical therapy